Thermal Effects in Complex Machining Processes Final Report of the DFG Priority Programme 1480 (Lecture Notes in Production Engineering,, 2018)
This contributed volume contains the research results of the priority programme (PP) 1480 "Modelling, Simulation and Compensation of Thermal Effects for Complex Machining Processes", funded by the German Research Society (DFG). The topical focus of this programme is the simulation-based prediction and compensation of thermally induced workpiece deviations and subsurface damage effects. The approach to the topic is genuinely interdisciplinary, covering all relevant machining operations such as turning, milling, drilling and grinding. The target audience primarily comprises research experts and practitioners in the field of production engineering, but the book may also be beneficial for graduate students.